1997
DOI: 10.1111/j.1348-0421.1997.tb01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Neutralizing Epitope on Human Cytomegalovirus Glycoprotein B in Japanese: Correlation of Serologic Response with HLA‐Type

Abstract: Antigenic domain 1 (AD-1), located between amino acids 608 and 625 of human cytomegalovirus (CMV) gB protein, is the major domain recognized by neutralizing antibodies. Amino acids 552 to 630 are essential for the binding of neutralizing antibodies. We developed an enzyme-linked immunosorbent assay (ELISA) to detect antibodies against a fusion protein containing amino acid residues 549 to 644 of the gB polypeptide and maltose binding protein (MBP). Of 180 seropositive samples, 106 (58.9%) showed positive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Kropff et al [1993] reported a low prevalence of 44% of AD1-ELISA reactive antibodies in serum specimens with low titers of neutralizing antibodies. Wada et al [1997] found a seroprevalence of 59% in HCMV seropositive individuals using a similar ELISA approach. This is consistent with results described in this communication concerning the reactivity of serum samples from HCMV seropositive blood donors with either procaryotically expressed AD1 or an AD1peptide.…”
Section: Discussionmentioning
confidence: 85%
“…Kropff et al [1993] reported a low prevalence of 44% of AD1-ELISA reactive antibodies in serum specimens with low titers of neutralizing antibodies. Wada et al [1997] found a seroprevalence of 59% in HCMV seropositive individuals using a similar ELISA approach. This is consistent with results described in this communication concerning the reactivity of serum samples from HCMV seropositive blood donors with either procaryotically expressed AD1 or an AD1peptide.…”
Section: Discussionmentioning
confidence: 85%
“…P ! .035 Therefore, it appears that patients with MS have an unusual and perhaps genetically influenced [53][54][55] immunologic relationship with HHV-6 in that they are even less able to effectively control their active HHV-6 infections than are other patients receiving severe iatrogenic immunosuppressive therapy.…”
Section: Resultsmentioning
confidence: 98%
“…Another possible association between HLA and CMV infection is in the production of antibodies. It has been reported that deficiencies in the production of neutralizing antibodies against CMV gB in certain HLA types may lead to increased susceptibility (Wada, Mizuno et al 1997). In this report, subjects with HLA-DR9 had a higher positive rate against CMV gB and subjects with HLA-DR15 had a lower positive rate against gB.…”
Section: Association Of Hla-dr With Strain-specific Antibodiesmentioning
confidence: 51%